Relative DOA estimation method for UAV swarm based on phase difference information without fixed anchors - Han, Yi; Zhang, Jingjing; Luo, Jinglin (Scientific reports, 2025)
A key challenge for unmanned aerial vehicle (UAV) swarms is achieving inter-aircraft relative direction of arrival (DOA) estimation in global navigation satellite system (GNSS) denied environments without relying on fixed base stations. This paper proposes a Ultra-wide Bandwidth (UWB) based method where each UAV acts as both a transmitter and receiver, effectively functioning as a mobile base station. A theoretical framework for all-directional DOA estimation using a regular tetrahedral array is derived, resolving phase ambiguities via a genetic algorithm (GA) with phase difference information. Simulation results demonstrate that GA-UWB algorithm has a better performance than WP-UWB. When considering noise both in time difference and phase difference information, the algorithm proposed in this paper has a higher success rate.